The Importance of Entrepreneur Characteristic and Emotional Quotients as SME’S Competitive Advantage to Marketing Performance - Pranaditya Ari; Sabihah Khansa (SHS Web of Conferences)
The black swan event, Covid-19 pandemic has caused a multidimensional crisis that has hit not only Indonesia but the world. The negative impact paralyzes the business world, as job opportunities are getting narrower, the number of people who need work continues to increase, not mentioning the slowdown of Indonesian economy in the first half of 2024 resulting in an increasing unemployment rate. Many workers experienced termination of employment then become successful SME’S entrepreneurs. This phenomenon is a problem as well as the right solution to face the crisis is to develop an entrepreneurial spirit. This study aims to figure the antecedent of successful marketing performance for entrepreneur based on resource-based theory by analysing the relation between entrepreneur characteristic and emotional quotients as SME’S competitive advantage. The study outcomes revealed that all five hypotheses are supported, as entrepreneur characteristics influences positively competitive advantage and entrepreneur characteristics influences positively marketing performance. It’s also empirically tested that emotional quotient influences positively competitive advantage and emotional quotients influences positively marketing performance. Ultimately, competitive advantage influences positively marketing performance.The population in this study is retail SME’S in the Semarang City area. The analysis method was carried out with SEM AMOS 2.0